When Less Is More: The Benefits of Limits on Executive Pay - Cebon, Peter; Hermalin, Benjamin E. (Review of Financial Studies, 2015)
We derive conditions under which limits on executive compensation can enhance efficiency and benefit shareholders (but not executives). Having its hands tied in the future allows a board of directors to credibly enter into relational contracts with executives that are more efficient than performance-contingent contracts. This has implications for the ideal composition of the board. The analysis also offers insights into the political economy of executive-compensation reform.